'Is Grandma Still There?' A Pastoral and Ethical Reflection on the Soul and Continuing Self-identity in Deeply Forgetful People. (June 2016) - Post, Stephen G.
This metaphysical and pastoral reflection focuses on a question that over several decades has been posed to me by many family caregivers for deeply forgetful people (persons with dementia). The question may take different forms: Is my loved one still there underneath all of this confusion? Is my loved one's soul still present? Will she come to rest fully intact in the arms of a Supreme Being? Could she be 'gone' but already somewhere experiencing the fullness of divine love? This reflection provides a pastoral response to this big question that has to do with the need to find meaning in caring for deeply forgetful people.